Analyse and Measure the Operational Risk in Chinese Commercial Bank - Gao, Jingjing (2019)
Operational risk is one of the oldest risks facing by commercial banks, and it can emerge in every aspect of the business environment. The huge losses due to operational risk is increasing in recent years. Therefore, commercial banks must control and manage operational risk. Due to the Chinese banking industry still in the process of reform, this study mainly focuses on the current situation of operational risk in China. This dissertation is written to identify an accurate measurement method that can help the commercial bank make a relatively accurate judgment on operational risk and find the main causes of operational risk. Then analyze the current situation of operational risk management in China and provide some useful recommendations about improving the management level of Chinese commercial banks based on some successful cases and the causes that analyzed.